The History, Status, Gaps, and Future Directions of Neurotoxicology in China - Cai, Tongjian (Environ Health Perspect, 2016)
BACKGROUND: Rapid economic development in China has produced serious ecological, environmental, and health problems. Neurotoxicity has been recognized as a major public health problem. The Chinese government, research institutes, and scientists conducted extensive studies concerning the source, characteristics, and mechanisms of neurotoxicants. OBJECTIVES: This paper presents, for the first time, a comprehensive history and review of major sources of neurotoxicants, national bodies/legislation engaged, and major neurotoxicology research in China. METHODS: Peer-reviewed research and pollution studies by Chinese scientists from 1991 to 2015 were examined. PubMed, Web of Science and Chinese National Knowledge Infrastructure (CNKI) were the major search tools. RESULTS: The central problem is an increased exposure to neurotoxicants from air and water, food contamination, e-waste recycling, and manufacturing of household products. China formulated an institutional framework and standards system for management of major neurotoxicants. Basic and applied research was initiated, and international cooperation was achieved. The annual number of peer-reviewed neurotoxicology papers from Chinese authors increased almost 30-fold since 2001. CONCLUSIONS: Despite extensive efforts, neurotoxicity remains a significant public health problem. This provides great challenges and opportunities. We identified 10 significant areas that require major educational, environmental, governmental, and research efforts, as well as attention to public awareness. For example, there is a need to increase efforts to utilize new in vivo and in vitro models, determine the potential neurotoxicity and mechanisms involved in newly emerging pollutants, and examine the effects and mechanisms of mixtures. In the future, we anticipate working with scientists worldwide to accomplish these goals and eliminate, prevent and treat neurotoxicity. CITATION: Cai T, Luo W, Ruan D, Wu YJ, Fox DA, Chen J. 2016. The history, status, gaps, and future directions of neurotoxicology in China. Environ Health Perspect 124:722–732; http://dx.doi.org/10.1289/ehp.1409566